2010
DOI: 10.3748/wjg.v16.i12.1449
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in Middle Eastern and North African countries: A new burden?

Abstract: Celiac disease (CD) is now recognized as a common disorder among Middle Eastern (ME) and North African (NA) populations. The aim of this review is to assess the available data regarding CD in the ME and NA and to compare this information with that of Western countries. A literature review was performed using the electronic databases PubMed and Medline (1950-2008) as search engines, and "celiac disease" was used as a Mesh term. The search was limited to ME and NA countries. The prevalence of CD in ME and NA cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 85 publications
4
74
0
3
Order By: Relevance
“…In addition, gluten-free products are generally more expensive than their counterparts, and their availability varies around the world, especially in developing countries (28,29). It is estimated that gluten contamination of GFDs occurs for 32 to 55% of CD patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gluten-free products are generally more expensive than their counterparts, and their availability varies around the world, especially in developing countries (28,29). It is estimated that gluten contamination of GFDs occurs for 32 to 55% of CD patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the CD patients have HLA DQ2 and DQ8 alleles which are responsible from 40% of genetic susceptibility to CD [9]. It has been indicated that the prevalance of DQ2 and DQ8 genes differs according to the different populations [18].…”
Section: Discussionmentioning
confidence: 99%
“…The new European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) criteria is published in 2012 and recently the diagnosis of CD, according to this new criteria, is based on: gluten-dependent symptoms, Human Leukocyte Antigen (HLA) typing (presence of HLA-DQ2 and/or DQ8), CD-specific antibodies levels (anti-tissue transglutaminase type 2 (anti-TG2), antiendomysium (EMA) and characteristic histological changes [8]. CD is one of the most common genetic disorders with a prevalance of 1-2.67%, recently [9]. There is an increased risk (5-10%) of CD in first-degree relatives of CD patients [10].…”
mentioning
confidence: 99%
“…Various studies still report that diarrhea is the most common symptom in celiac patients (19)(20)(21). While one of the most common causes of chronic diarrhea in Middle East and North Africa is CD, the incidence of CD was reported to be 4.7% in patients presenting with diarrhea and growth failure in Egypt (22)(23)(24). On the other hand, some studies have reported that diarhhea has been observed with a lower frequency in recent years (25,26).…”
Section: Discussionmentioning
confidence: 99%